PENGARUH TEKANAN INJEKTOR DAN TEMPERATUR BAHAN BAKAR MINYAK JELANTAH TERHADAP UNJUK KERJA MOTOR DIESEL 4 LANGKAH 1 SILINDER DENGAN BEBAN 2000 WATT - Zaenal Fanani Kresna; Sidi Pranowo; Haryono Edi (Politeknik Perkapalan Negeri Surabaya, 2018)
The use of petroleum fuel is currently higher. Although there have been many studies of biodiesel, but in the production process requires lot of money and complicated production process. Therefore, this is used waste cooking oil as fuel. This study is conducted to get optimum injection pressure and fuel temperature when use waste cooking oil as fuel. The aims is to know how much effect of injector pressure and fuel temperature of waste cooking oil to the diesel engine performance. This research uses experimental method. There are 4 varations of injector pressure 130 bar, 140 bar, 150 bar, 160 bar. Variations of fuel temperature are 80 °C, 90 °C, 100 °C, 110 °C. The variation of load is 2000 watt at 1200 rpm, 1300 rpm , 1400 rpm, 1500 rpm. The result is the optimum injector pressure on variation 140 bar and fuel temperature of waste cooking oil is 90 °C. Trendline of SFC value when waste cooking oil used as fuel was lower than when used pertamina dex as fuel at various loads. Injector pressure and fuel temperature of waste cooking oil have contribution of 11,063% and 7,444% to performance of diesel engine.